Understanding sexual dysfunction in french military service member with PTSD: findings from a descriptive study - Gilles Sipahimalani; Marion Remadi; Antoine Baldacci; Thibaut Long-Depaquit; Arthur Peyrottes; Marie Dusaud; Emeric Saguin (Basic and Clinical Andrology)
Abstract Background Sexual dysfunction is a serious and frequently underrecognized consequence of Post-Traumatic Stress Disorder (PTSD), with profound implications on quality of life. This study aimed to characterize sexual dysfunction observed in French military personnel suffering from PTSD. Results This retrospective study included 32 male French military personnel diagnosed with PTSD who participated in a sexual dysfunction screening program at a French National Military Hospital between October 2023 and August 2024. The mean age of participants was 40 years. The Post-Traumatic Stress Disorder Checklist Scale version DSM-5 (PCL-5) and the International Index of Erectile Function version 5 (IIEF-5) were used to assess PTSD and sexual dysfunction severity. Seventy-two percent (n = 23) reported at least one sexual dysfunction, with sexual desire dysfunction being the most common sexual health issue. Approximately 70% perceived the impact of sexual dysfunction on quality of life as high or very high. Significant correlations were found between PCL-5 and IIEF-5 scores, suggesting that the severity of PTSD symptoms impacts sexual health, specifically concerning cluster B (re-experiencing symptoms) and cluster D (negative thoughts and/or feelings) symptoms. Psychiatric symptoms were the primary risk factor, followed by psychotropic treatment and personal factors. Conclusion This study highlights the high prevalence of sexual dysfunction among French military personnel with PTSD. The diversity of the clinical presentations and risk factors emphasize the need for comprehensive sexual health assessments in PTSD management. Personalized care strategies targeting both psychiatric and sexual health issues are essential for improving outcomes in this population.